Angiotensin Receptor Blockers Potentiate the Protective Effect of Branched‐Chain Amino Acids on Skeletal Muscle Atrophy in Cirrhotic Rats. Issue 24 (1st November 2021) - Takeda, Soichi; Kaji, Kosuke; Nishimura, Norihisa; Enomoto, Masahide; Fujimoto, Yuki; Murata, Koji; Takaya, Hiroaki; Kawaratani, Hideto; Moriya, Kei; Namisaki, Tadashi; Akahane, Takemi; Yoshiji, Hitoshi
Abstract : Scope: This study investigated the combined effect of the angiotensin II (AT‐II) receptor blocker losartan and branched‐chain amino acids (BCAAs) on skeletal muscle atrophy in rats with cirrhosis and steatohepatitis. Method and Results: Fischer 344 rats are fed a choline‐deficient l ‐amino acid‐defined (CDAA) diet for 12 weeks and treated with oral losartan (30 mg kg −1 day −1 ) and/or BCAAs (Aminoleban EN, 2500 mg kg −1 day −1 ). Treatment with losartan and BCAAs attenuated hepatic inflammation and fibrosis and improved skeletal muscle atrophy and strength in CDAA‐fed rats. Both agents reduced intramuscular myostatin and pro‐inflammatory cytokine levels, resulting in inhibition of the ubiquitin–proteasome system (UPS) through interference with the SMAD and nuclear factor‐kappa B pathways, respectively. Losartan also augmented the BCAA‐mediated increase of skeletal muscle mass by promoting insulin growth factor‐I production and mitochondrial biogenesis. Moreover, losartan decreased the intramuscular expression of transcription factor EB (TFEB), a transcriptional inducer of E3 ubiquitin ligase regulated by AT‐II. In vitro assays illustrated that losartan promoted mitochondrial biogenesis and reduced TFEB expression in AT‐II‐stimulated rat myocytes, thereby potentiating the inhibitory effects of BCAAs on the UPS and caspase‐3 cleavage. Conclusion: These results indicate that this regimen could serve as a novel treatment for patients with sarcopenia and liver cirrhosis. Abstract : This study demonstrates that angiotensin‐II receptor blockers efficiently augment the inhibitory effects of branched‐chain amino acids on skeletal muscle atrophy in a rat liver cirrhosis model, which is based on the prevention of liver inflammation and fibrosis resulting in the myokine signaling inhibition and insulin growth factor‐1 restoration as well as promoted mitochondrial biogenesis in myotubes.